(untitled) (Journal of Medicine, 2016)
Objective: To assess knowledge about risk factors and complication of coronary heart disease (CHD). Method: It was a cross-sectional type of study and research participants were one of the family members of the patient suffering from coronary heart disease. The sample population and unit of sample were households. A total of 147 participants were selected from Inpatient Department of the National Institute of Cardio-Vascular Disease, Sher-e-Bangla Nagar, Dhaka from January 2013 to July 2013 following purposive method of sampling on the basis of defined selection criteria. The research instrument was a pre-tested face-to-face interviewer questionnaire. Knowledge level of the respondents was assessed using Likert type of scale incorporate in the questionnaire. Results: Most of the research participants (95.2%, n=140) were educated and only 4.8% (n=07) found illiterate. In profession, 29.9% (n=44) of the respondents were housewife, 36.1% (n=53) service holder, 22.4% (n=24) businessmen and 11.6% (n=17) students. Their average monthly income was Tk. 9149±108 and their family income was Tk. 3448±7 in average. The mean age of the respondents was 33.1±6.8 years of which 76.9% (n=113) married and rest of them (23.1%, n=34) unmarried. Among the respondents, 50.3(n=74) were male and 49.7% (n=73) female respectively. The level of knowledge of the respondents about risk factors and complication of coronary heart disease on the basis of gender, education and occupation was assessed. Of them, 75.5% (n=111) had poor knowledge about risk factors and complication of coronary heart disease, 24.5% (n=36) satisfactory knowledge and none of them had good knowledge about it which was significantly associated with the level of education, occupational and monthly income status of the respondents. Conclusion: An individual can modify or avoid many risk factors to prevent CHD or minimize the complication of CHD except age and genetic factors. However, need based health education and behavioral change intervention programs among the risk populations (target populations) and to ensure easy access in public healthcare facilities may be the most important applicable ways to control and/or prevention of CHD in Bangladesh. J MEDICINE July 2016; 17 (2) : 84-90